Thermal analysis of polymer bonded explosives based on cyclic nitramines - Yan, Qilong (Univerzita Pardubice, 2015)
In this project, the thermal reactivity of cyclic nitramines based PBXs were investigated by means of TG and DSC, XRD, FTIR and SEM techniques, as well as molecular dynamic (MD) simulations. The kinetic parameters and physical models were determined based on TGA data using master plots and combined kinetic analysis methods, where the overlapped peaks were properly separated before kinetic evaluations. The obtained kinetic triplets were used to predict the storage lives and constant rate decomposition temperature profiles of involved PBXs. The mechanical sensitivities used herein are taken from the literature. Based on comparative investigation and correlations, the inherent mechanisms for the effects of the polymer binders on decomposition kinetics and mechanical sensitivities were found, which have been supported by the molecular dynamic simulations.
Termická analýza polymery pojených výbušin na bázi cyklických nitraminů
Keywords: PBXs; polymerní pojiva; cyklické nitramines; kinetika rozkladu; reakce modelu; molekulární dynamické simulace; polymer binders; cyclic nitramines; decomposition kinetics; reaction model; molecular dynamics simulation